Uncertainty analysis of active SHM system - Thiene,M; Khodaei,S; Aliabadi,MH (2016)
Structural Health Monitoring (SHM) techniques have gained an increased interest to be utilised alongside NDI techniques for aircraft maintenance. However, to take the SHM methodologies from the laboratory conditions to actual structures under real load conditions requires them to be assessed in terms of reliability and robustness. In this work, a statistical analysis is carried out for an SHM system for damage detection and characterisation in composite structures. The sensitivity of the platform to parameters such as noise, sensor failure, placement tolerances and bonding has been investigated and reported.